2023
DOI: 10.1098/rspa.2022.0565
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent wave-balance exchanges in the ocean

Abstract: Oceanic flows are turbulent and multi-scale in nature, and are composed of fast internal waves and slowly evolving balanced eddies. Contrary to conventional wisdom in physical oceanography, the past two decades of in situ , satellite altimeter and realistically forced global scale ocean model outputs have revealed that internal gravity waves can have comparable or higher energy levels than geostrophically balanced flows at 10–100 km scales in different parts of the world’s oceans. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 231 publications
0
1
0
Order By: Relevance
“…(2018) analyzed contributions of balanced and unbalanced motions in kinetic energy and sea surface height, and found that the relative contributions of two classes of motions to various surface fields are complex and dependent on multiple factors, such as seasonal, geographical and the distribution of low and high eddy kinetic energy regions. Further, only recently has attention been given to the effects that internal waves may have on the mesoscale and submesoscale structures, and to the possibility for substantial energy exchanges and modifications to the cross‐scale energy cascades (J. Thomas & Daniel, 2021; J. Thomas & Vishnu, 2022; J. Thomas, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…(2018) analyzed contributions of balanced and unbalanced motions in kinetic energy and sea surface height, and found that the relative contributions of two classes of motions to various surface fields are complex and dependent on multiple factors, such as seasonal, geographical and the distribution of low and high eddy kinetic energy regions. Further, only recently has attention been given to the effects that internal waves may have on the mesoscale and submesoscale structures, and to the possibility for substantial energy exchanges and modifications to the cross‐scale energy cascades (J. Thomas & Daniel, 2021; J. Thomas & Vishnu, 2022; J. Thomas, 2023).…”
Section: Introductionmentioning
confidence: 99%